Analisis Hybrid Bisnis Model Pada Startup di Indonesia - Tiawan Tiawan; Made Artana; I Gede Juliana Eka Putra; Linda Lorenza Hafifah (Jurusan Teknik Elektro Fakultas Teknik Universitas Halu Oleo, 2023)
A hybrid is a thing, object, or technology that combines two different things, objects, or technology, but still maintains both the properties and characteristics of the two elements. Digital transformation has created an information revolution, removed boundaries, created a knowledge-based global market, and resulted in MSMEs finding new business models, conducting business transactions, and cooperation in all fields to form economic strength, there are several business models such as BMC (Business Model Canvas). Lean Canvas, and many more business models in the Startup field. All digital activities, even transaction activities are carried out digitally because they are faster, more effective, and efficient. To improve their capabilities, MSMEs start with developing strategies to become a hybrid business, as well as online and offline business models that have been formed in combination, this business model is used as a reference both when startups are pitching and running their business. Therefore, using an effective and efficient hybrid business model is needed to achieve the goals of startup players in obtaining investment or increasing their digital business.